DOTA-functionalized polylysine: a high number of DOTA chelates positively influences the biodistribution of enzymatic conjugated anti-tumor antibody chCE7agl - Grünberg, Jürgen; Sarko, Dikran; Mier, Walter (PLOS ONE, 2013)
Site-specific enzymatic reactions with microbial transglutaminase (mTGase) lead to a homogenous species of immunoconjugates with a defined ligand/antibody ratio. In the present study, we have investigated the influence of different numbers of 1,4,7,10-tetraazacyclododecane-N-N′-N′′-N′′′-tetraacetic acid (DOTA) chelats coupled to a decalysine backbone on the in vivo behavior of the chimeric monoclonal anti-L1CAM antibody chCE7agl. The enzymatic conjugation of (DOTA)1-decalysine, (DOTA)3-decalysine or (DOTA)5-decalysine to the antibody heavy chain (via Gln295/297) gave rise to immunoconjugates containing two, six or ten DOTA moieties respectively. Radiolabeling of the immunoconjugates with 177Lu yielded specific activities of approximately 70 MBq/mg, 400 MBq/mg and 700 MBq/mg with increasing numbers of DOTA chelates. Biodistribution experiments in SKOV3ip human ovarian cancer cell xenografts demonstrated a high and specific accumulation of radioactivity at the tumor site for all antibody derivatives with a maximal tumor accumulation of 43.6±4.3% ID/g at 24 h for chCE7agl-[(DOTA)-decalysine]2, 30.6±12.0% ID/g at 24 h for chCE7agl-[(DOTA)3-decalysine]2 and 49.9±3.1% ID/g at 48 h for chCE7agl-[(DOTA)5-decalysine)]2. The rapid elimination from the blood of chCE7agl-[(DOTA)-decalysine]2 (1.0±0.1% ID/g at 24 h) is associated with a high liver accumulation (23.2±4.6% ID/g at 24 h). This behavior changed depending on the numbers of DOTA moieties coupled to the decalysine peptide with a slower blood clearance (5.1±1.0 (DOTA)3 versus 11.7±1.4% ID/g (DOTA)5, p<0.005 at 24 h) and lower radioactivity levels in the liver (21.4±3.4 (DOTA)3 versus 5.8±0.7 (DOTA)5, p<0.005 at 24 h). We conclude that the site-specific and stoichiometric uniform conjugation of the highly DOTA-substituted decalysine ((DOTA)5-decalysine) to an anti-tumor antibody leads to the formation of immunoconjugates with high specific activity and excellent in vivo behavior and is a valuable option for radioimmunotherapy and potentially antibody-drug conjugates (ADCs).